METHOD OF NAHWU IN ARABIC LEARNING - Asy'ari, M. (AKADEMIKA: Jurnal Pemikiran Islam, 2019)
Abstract Language is very important and the impression that Nahwu is a difficult science to learn, especially by Muslims. As one of the basic sciences in Arabic, Nahwu's science cannot be ignored because without Nahwu's knowledge, Arabic will become chaotic and the order of words and sentences will be disorganized. Therefore, in learning Arabic, it is important to know Nahwu's knowledge, even though this method of teaching science is quite widely practiced by nahwu teachers, but students continue to face difficulties in learning it. Therefore, it is necessary to use suitable teaching methods and appropriate steps and subject matter that must be prioritized to be taught to students, so as to facilitate them in learning Nahwu science.[1] Related to this, there are a number of issues that need to be discussed, namely: What is the importance of learning nahwu, especially by students who want to communicate in Arabic ?; What method should be used so that students can learn nahwu easily? Here are some important questions that will be discussed in this article. Keywords: Nahwu, Learning, amd Arabic